Gordon College (Journal of the College of Basic Education, 2022)
Gordon College is one of the most prominent British achievements, as it was established by Lord Kitchener in memory of the LordGordon, who was killed by the Mahdi forces in the country of Sudan 0, which was a rehabilitation for the BritishIn retaliation for the Gordon 0 bomb, and to be an edifice of foreign science and culture. And she doesIt became so, but by turning it into a beacon that guides the Sudanese people to the path of salvation; It was for the professorsThe Egyptians have a great role. And many of its graduates became; who completed his education in it or who was unable to complete it;leaders of the political movement, awareness and bitter struggle against colonialism; Do not be deceived by the local and global conditionsI have announced all this; And that college could not live in isolation, no matter how hard the English tried to isolate it from itevents